Analysis Of Implementation Of Drug Inventory Control Using Abc-Eoq-Rop-Ss Method At Arun Hospital Lhokseumawe - Miftah Asthariq; Sri Wahyuni Nasution; Sri Lestari Ramadhani Nasution (CV. Inara, 2022)
The pharmaceutical installation of Arun Hospital Lhokseumawe currently uses the consumption method in controlling drug supply, this method has a weakness, in the shortcomings and advantages of drugs that are difficult to rely on, but the ABC-EOQ-ROP-SS method can answer the weaknesses of the consumption method. The purpose of this study is to provide a choice of other methods for controlling drug inventory at Arun Hospital Lhokseumawe. This study is a mix-method study with retrospective data for quantitative data and primary data for qualitative data. The study was conducted at Arun Hospital Lhokseumawe from October 2021 to November 2021. The research population used was all drug items during August 2020, totaling 269 items. The ABC method is used to group drug items into 3 groups, the EOQ method is used to determine the number of drugs to be ordered in the next order, the ROP method is used to determine when to order drugs at the next time and the SS method is used to determine safety stock. The results showed the results of the ABC method group A were 59 items, B were 64 items, and C were 146 items, the results of the EOQ method group A were 414 - 159, B was 414 – 159, and C was 778 - 1407 for certain types of drugs, the results of the method The ROP of group A were 12,027 – 962, group B was 6014 – 20,045 and group C was 3007 – 200 for certain types of drugs. The results of the SS method group A were 627 – 50, B was 314 -1054, and C was 157 – 11 for certain drug groups. Suggestions for Arun Hospital Lhokseumawe to try methods of controlling drug supplies other than the consumption method so that efficiency in managing drug supplies can be increased. good and can provide training to human resources at the pharmacy installation of Arun Hospital Lhokseumawe related to controlling the supply of drug needs.